Proposal of evaluating method of starting technique for competitive swimmers: utilization of stop-watch - Sato, S.; Demura, S.; Nakada, M.; Kitabayashi, T.; Noguchi, T. (Japanese Journal of Sciences in Swimming and Water Exercise, 2004)
We proposed a convenient method, applicable in a field setting, for evaluating starting techniques for competitive swimmers. This study aimed to examine whether a stopwatch is applicable in this evaluation method. Three procedures were used to measure the passing time at each reference point: (1) using a stopwatch (SW); (2) from video footage using the single frame step function in the video camera (VTR); (3) from video footage using a stopwatch (VTR+SW). Reference points were marked on a rope at 50 or 100 cm intervals in the starting phase; that is, from the start point to 15 m. Video recordings were made using a digital video camera (1/30 sec per frame), and video recordings and measurements of passing time using a stopwatch were conducted by traveling alongside the swimmer on the poolside. In both SW and VTR+SW, passing time could not be accurately measured at 50 cm intervals, while measurements at 100 cm intervals were possible with SW, but not VTR+SW. The autocorrelation coefficients between swimming velocity curves of the VTR and SW measurements at 100 cm intervals were 0.70 with a lag of 0 and 0.84 with a lag of 1, respectively. Thus, by using 100 cm intervals similar swimming velocity curves could be obtained using SW and VTR+SW. The swimming velocity curve calculated from 100 cm interval measurements provided an outline of starting techniques, although the amount of information decreased compared with the swimming velocity curve obtained with VTR at 50 cm intervals.